Economic significance of some productive traits in Sarda sheep farming systems - Natale A.; Oppia P.; Sanna S.R.; Carta A.; Ligios S. (Analysis and definition of the objectives in genetic improvement programmes in sheep and goats. An economic approach to increase their profitability, 2000)
A description of Sardinian dairy sheep farming systems and an analysis of the farm economic results were reported in order to verify the genetic improvement objectives chosen for Sarda sheep. Milk yield per ewe showed, by far, the greatest effect on sheep activity margins of Sardinian farms. So, the selection judgements expressed in the early 70s for Sarda sheep, even in the light of recent milk price decrease, still preserve their economic importance.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/11/18-20, Zaragoza (Spain)